RISK PERCEPTION OF RETAIL INVESTORS TOWARDS EQUITY INVESTMENT IN INDIAN STOCK MARKET (International Journal of Food and Nutritional Sciences, 2022)
The Indian stock market has emerged as a prominent avenue for wealth generation and economic participation, underpinned by its vibrant equity culture and robust regulatory framework. Despite this growth, retail investors in India demonstrate a cautious approach towards equity investment, influenced significantly by their perception of risk. Risk perception, a multifaceted construct shaped by psychological, demographic, and market-related factors, directly affects investment behavior and market participation. This research paper examines the risk perception of retail investors in the Indian stock market, focusing on the interplay of demographic variables such as age, income, and education, along with psychological biases like loss aversion, overconfidence, and herd behavior.The study adopts a mixed-method approach, incorporating quantitative surveys and qualitative interviews with 100 retail investors from diverse socioeconomic backgrounds. Statistical tools and thematic analysis reveal how financial literacy, market volatility, and past experiences influence risk attitudes. Findings indicate that younger and higher-income investors display a greater propensity for risk, whereas loss aversion and limited financial literacy deter participation. Furthermore, external shocks, such as market crashes during the COVID-19 pandemic, exacerbate risk perception, underscoring the need for resilience-building strategies.This paper highlights the importance of targeted financial education, regulatory reforms, and technological innovations in mitigating risk perception barriers. It provides actionable recommendations for policymakers, market regulators, and financial institutions to foster greater retail participation, thereby contributing to a more inclusive and resilient financial ecosystem. The insights gleaned from this research aim to bridge the gap between perceived and actual risks, empowering retail investors to make informed equity investment decisions.